2019
DOI: 10.1111/jicd.12390
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlations of temporomandibular disorders in Northern Jordan using diagnostic criteria axis I

Abstract: Aim:The aim of the present study was to document the prevalence and possible correlations of temporomandibular disorders (TMD) in a sample of participants from Northern Jordan. Methods:A total of 368 adult participants were consecutively selected from visitors to a major health facility in Northern Jordan and examined according to the diagnostic criteria (DC) for TMD (DC/TMD) protocol. Patients with conditions that could interfere with TMD diagnosis were excluded. Pearson correlation and analysis of variance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“… 39 In the present study, a score of ≥3 on the pain screener indicated self-reported pain-related TMDs, the prevalence of which was 22.2%, which is slightly higher than reported in studies conducted in northern Jordan (20.7%) and Serbia (16.4%). 40 , 41 A self-report pain instrument was used in the present study, so some patients with dental pain (which can mimic TMD pain) may have been included. Therefore, the real prevalence of pain-related TMDs may be lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 In the present study, a score of ≥3 on the pain screener indicated self-reported pain-related TMDs, the prevalence of which was 22.2%, which is slightly higher than reported in studies conducted in northern Jordan (20.7%) and Serbia (16.4%). 40 , 41 A self-report pain instrument was used in the present study, so some patients with dental pain (which can mimic TMD pain) may have been included. Therefore, the real prevalence of pain-related TMDs may be lower.…”
Section: Discussionmentioning
confidence: 99%
“…A higher proportion of women than men showed pain-related TMDs in this study ( Table 2 ), a finding in accord with those of several other studies in a range of settings. 3 , 15 , 35 , 40 , 42 44 This sex difference in pain may stem from interactions between biological, psychological and sociocultural factors, although the exact mechanism underlying these interactions is unknown. 45 There is evidence from large-sample case-control studies that women have greater pain sensitivity, 39 that female sex is more strongly associated with TMD-related genes 46 and that women have greater odds of having depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria were based on previously conducted studies in the same setting [4]. In brief, participants had to be at least 18 years old, living in Northern Jordan, fully dentate and not wearing removable partial or complete dentures and not having odontogenic pain complaint at the time of examination (as this could mask TMD or other orofacial pain) or a recent history of trauma or surgery to the maxillofacial structures.…”
Section: Methodsmentioning
confidence: 99%
“…There is, generally, an agreement in the literature that TMD is common, with prevalence rates in the population ranging between 10-15% for adults and 4-7% for adolescents [3]. Some reports suggested that TMD prevalence may even reach up to 27% in some populations [4,5]. Annual incidence of first-onset painful TMD from a large prospective study (OPERA) shows rates of 3-4% [6].…”
Section: Introductionmentioning
confidence: 99%
“…TMDs reflects a group of comorbid conditions and clinical issues in which the incidence of muscular dysfunction tend to be more common than those which are intra-capsular joint-related [ 26 , 27 , 28 ]. Myofascial disturbances arise from tension, fatigue or spasm of the masticatory muscles whereas intra-articular disorders derive from mechanical or inflammatory damage to the joint itself.…”
Section: Introductionmentioning
confidence: 99%